LEGAL RESPONSIBILITY OF PUBLIC TRANSPORT BUS DRIVERS DUE TO AN ACCIDENT WHICH CAUSED A PASSENGER TO DIE BASED LAW NUMBER 22 OF 2019 REGARDING TRAFFIC AND ROAD TRANSPORT (Study of the Decision of the Simalungun District Court Number 55/Pid.Sus/2019/PN Sim) - Muhammad Ansori Lubis (JURNAL DARMA AGUNG, 2022)
Traffic accidents result in many casualties, and perpetrators may be charged with murder due to negligence or negligence while driving. This application is regulated by Law No. 22 of 2009 on Road Traffic and Transportation. The research method is descriptive analysis, which leads to normative legal research, i.e. research with reference to legal norms, i.e. the study of library materials and secondary sources. Secondary data processed from primary legal data, secondary legal data, and tertiary legal data. As a result, Article 310, No. 22 of the Road Traffic Act of 2009 provides regulations for driver negligence resulting in death, and targets drivers who cause fatal accidents due to negligent driving. In the world of other people's death, punishable by imprisonment not exceeding six years or a fine not exceeding rupiah. 12,000,000.- (12 million) Rupiah. In the case of intentional death in a traffic accident that endangers the safety of road users by intentionally driving a motor vehicle in a dangerous manner, the determination of the criminal act as intentional negligence is governed by Article 311 of the Act. 22nd, 2009 on Road Traffic and Transportation.